Implikasi Yuridis Pembatasan Subjek Pelapor Dalam Delik Pencemaran Nama Baik Pasca Putusan Mahkamah Konstitusi Nomor 105/PUU-XXII/2024 - Afifah Mayaningsih (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
The Constitutional Court Decision (MK) No. 105/PUU-XXII/2024 has introduced a fundamental change in the enforcement of criminal law concerning defamation offenses, particularly with regard to the subject authorized to file a complaint. Prior to this decision, reports of defamation offenses under the Law on Information and Electronic Transactions (ITE Law) could be submitted by third parties. However, through this ruling, the Constitutional Court affirmed that only direct victims possess legal standing to report defamation offenses. This study aims to examine the regulation of defamation offenses under the ITE Law before and after Constitutional Court Decision Number 105/PUU-XXII/2024, as well as to analyze its juridical implications for the enforcement of the ITE Law. This research employs normative legal research with a statutory approach and a historical approach. The findings indicate that following the Constitutional Court’s decision, the authority to file complaints in defamation cases under the ITE Law is strictly limited to individuals who are directly harmed. Furthermore, the decision implies the necessity for regulatory adjustments through a revision of the ITE Law by the Government and the House of Representatives (DPR), particularly to clarify provisions that have generated multiple interpretations, in order to ensure legal certainty and the protection of human rights.